On the killing of mycobacteria by macrophages - Jordao, Luisa (2015)
Both pathogenic and non-pathogenic mycobacteria are internalized into macrophage phagosomes. Whereas the non-pathogenic types are invariably killed by all macrophages, the pathogens generally survive and grow. Here, we addressed the survival, production o